Difficulties of the Sixth Semester Students of English Language Study Program UIN Datokarama Palu in Translating Essential Idioms - Gulsam Gulsam; Muhammad Ihsan; Ruslin Ruslin; Hijrah Syam (Universitas Pahlawan Tuanku Tambusai, 2026)
Despite being an essential translation competency, idiom translation remains challenging for English Language Study Program students at UIN Datokarama Palu. Students often produce literal or unnatural translations due to limited cultural awareness, structural rigidity, dependence on translation technology, and difficulties in determining appropriate equivalents. This study aims to analyze the difficulties faced by sixth-semester students in translating English idioms and identify the factors influencing these difficulties. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected through questionnaires, while qualitative data were obtained through classroom observations and an analysis of students’ understanding of idiom translation. The findings reveal that students experienced moderate to high levels of difficulty in translating idioms. The main challenges involved determining appropriate lexical equivalents, selecting suitable translation strategies, and understanding cultural and pragmatic meanings. Limited vocabulary and a tendency to rely on literal translation also contributed to students’ difficulties. The findings indicate that idiom translation requires not only linguistic competence but also cultural and pragmatic awareness. Therefore, contextual and integrative instruction is recommended to help students produce more accurate and natural idiom translations